Efficient Vacuum Deposited P-I-N Perovskite Solar Cells by Front Contact Optimization - Babaei, Azin; Zanoni, Kassio P. S.; Gil-Escrig, Lidón; Pérez-del-Rey, Daniel; Boix, Pablo P.; Sessolo, Michele; Bolink, Henk J. (Frontiers in Chemistry, 2020)
Hole transport layers (HTLs) are of fundamental importance in perovskite solar cells, as they must ensure an efficient and selective hole extraction, and ohmic charge transfer to the corresponding electrodes. In p-i-n solar cells, the ITO/HTL is usually not ohmic, and an additional interlayer such as MoO3 is usually placed in between the two materials by vacuum sublimation. In this work, we evaluated the properties of the MoO3/TaTm (TaTm is the HTL N4,N4,N4",N4"-tetra([1,1'-biphenyl]-4-yl)-[1,1':4',1"-terphenyl]-4,4"-diamine) hole extraction interface by selectively annealing either MoO3 (prior to the deposition of TaTm) or the bilayer MoO3/TaTm (without pre-treatment on the MoO3), at temperature ranging from 60 to 200 °C. We then used these p-contacts for the fabrication of a large batch of fully vacuum deposited perovskite solar cells, using methylammonium lead iodide as the active layer. We show that the annealing at high temperature the MoO3/TaTm bilayers is required to obtain high rectification with low non-radiative recombination, due to an increase of the electrode work function and the formation of an ohmic interface with TaTm.